Developmental adverse effects of trace amounts of lead: Evaluation using zebrafish model - Komoike, Yuta; Matsuoka, Masato (Frontiers in Pharmacology, 2022)
Lead (Pb) is widely used as a raw material for various daily necessities in human civilization. However, Pb is a major toxicant and Pb poisoning has long been a global health concern. A large body of evidence has revealed that exposure to Pb causes a variety of adverse health effects. Meanwhile, experimental studies on the developmental effects caused by trace amounts of Pb remain to be fully conducted. Therefore, we aimed to provide direct experimental evidence of the adverse developmental effects of Pb exposure below the occupational regulatory standard concentrations using a zebrafish model. We also attempted to investigate the cellular stress response caused by such a trace amount of Pb at the individual level. Fertilized zebrafish eggs were exposed to 100 ppb Pb from 6 to 72 h post fertilization (hpf), the developmental period included within the mammalian implantation to birth. The embryos exposed to Pb did not show superficially evident morphological alterations or differences in viability compared with the controls until 72 hpf; however, they hatched earlier and were significantly shorter in body length than the controls at 48 and 72 hpf. Larvae that were exposed to Pb until 72 hpf and then cultured until 7 days post fertilization without Pb exhibited edema and inflation defects in the swim bladder. The reactive oxygen species level in the Pb-exposed embryos was similar at 24 hpf, slightly but significantly higher at 48 hpf, and lower than half that of the control at 72 hpf. Accordingly, the expression levels of oxidative stress response-related genes were analyzed, and five out of seven tested genes were upregulated in Pb-exposed embryos at 48 and 72 hpf. In addition, the endoplasmic reticulum (ER) stress related genes were upregulated at 48 hpf. These results indicate that exposure of embryos to trace amounts of Pb induces a transient increase in oxidative- and ER-stresses and results in weak hypotrophy and subsequent abnormalities later in development. Our findings may be key to understanding the total health effects of Pb exposure, and indicate that the zebrafish model is suitable for the investigation of developmental toxicity of pollutants such as Pb.